Community Stigma Among Schizophrenia During the Covid-19 Pandemic - Triyana Harlia Putri; Fransiska Tania (Universitas Aisyah Pringsewu, 2021)
Stigma is still a problem that is formulated in its prevention, but since the Covid-19 pandemic, there has been an increase in stigma in groups who are vulnerable to being infected with Covid-19. Several factors that influence societal stigma against schizophrenics have been identified. This study aims to determine the factors that influence the community's stigma against schizophrenics during the pandemic. The research design used a cross-sectional-online design, with purposive and snowball sampling techniques. The sample used was 400 people. The questionnaire used is the Community Attitude Towards the Mental Illness (CAMI) questionnaire. Bivariate data analysis using chi-square saw the sociodemographic correlation with stigma. Statistically, there is no correlation between community characteristics such as age, sex and employment status as evidenced by a value of p more than 0.05. However, there is a significant correlation between ethnicity, religion and education p less than 0.05. Thus, only ethnic, religious and educational factors influence the stigma in society for schizophrenics. Abstrak: Stigma masih menjadi permasalahan yang dirumuskan dalam pencegahannya, namun semenjak pandemi Covid-19, telah terjadi peningkatan stigma pada kelompok yang rentan terinfeksi Covid-19 ini. Beberapa faktor yang memengaruhi stigma masyarakat terhadap penderita skizofrenia telah diidentifikasi. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang memengaruhi stigma masyarakat terhadap penderita skizofrenia selama pandemi. Desain penelitian ini menggunakan rancangan crosssectional-online, dengan teknik pengambilan sampel purposive serta snowball. Sampel yang digunakan sebanyak 400 orang. Kuesioner yang digunakan adalah kuesioner Community Attitude Towards the Mental Illness (CAMI). Analisa data bivariat menggunakan chi-square melihat korelasi sosiodemografi dengan stigma. Secara statistik untuk tidak ada korelasi antara karakteristik masyarakat seperti umur, jenis kelamin dan status pekerjaan di buktikan dari nilai p lebih dari 0.05. Namun terdapat korelasi yang signifikan antara suku, agama dan pendidikan p kurang dari 0.05. Sehingga, hanya faktor suku, agama dan pendidikan yang memengaruhi stigma pada masyarakat pada penderita skizofrenia.